2017
DOI: 10.1590/1678-4162-9175
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de tiroxina materna associado ao hipertireoidismo pós-natal reduz o crescimento ósseo e o perfil proliferativo e angiogênico das cartilagens de crescimento de ratos

Abstract: RESUMOForam estudados os efeitos do excesso da tiroxina materna associado ao hipertireoidismo pós-natal sobre o crescimento ósseo e o perfil proliferativo e angiogênico das cartilagens. Dezesseis ratas Wistar adultas foram distribuídas nos grupos tratados com L-tiroxina e controle. A prole do grupo tratado recebeu L-tiroxina do desmame até 40 dias de idade. Ao desmame, foi realizada dosagem plasmática de T 4 livre nas mães. Na prole, foram realizados: dosagem plasmática de T 3 total e T 4 livre, morfometria da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…During hypothyroidism, the growth plates of rodents have a higher apparent heparan sulfate content as revealed by Alcian blue critical-electrolyte-concentration histochemistry [31] and the greater immunohistochemical expression of heparan sulfate [32]. In contrast, we have previously reported that excess maternal T4 reduces the intensity of PAS staining in the cartilaginous epiphysis of neonates but does not significantly alter Acan expression [23,33]. Therefore, the present study is complementary to the previously published report, quantitatively demonstrating a decrease in the percentage of PAS+ areas and downregulated Acan expression in the chondrocyte culture of neonates with maternal hyperthyroidism.…”
Section: Discussionmentioning
confidence: 92%
“…During hypothyroidism, the growth plates of rodents have a higher apparent heparan sulfate content as revealed by Alcian blue critical-electrolyte-concentration histochemistry [31] and the greater immunohistochemical expression of heparan sulfate [32]. In contrast, we have previously reported that excess maternal T4 reduces the intensity of PAS staining in the cartilaginous epiphysis of neonates but does not significantly alter Acan expression [23,33]. Therefore, the present study is complementary to the previously published report, quantitatively demonstrating a decrease in the percentage of PAS+ areas and downregulated Acan expression in the chondrocyte culture of neonates with maternal hyperthyroidism.…”
Section: Discussionmentioning
confidence: 92%